NOTE ON THE NATURAL PEARL OF PLACENTA PLACENTA (LINNAEUS) - Murty, V Sriramachandra (Indian Journal of Fisheries, 2011)
There is an extensive bed of Placenta placenta in the Kakinada Bay. About 26.2% of the population contains natural pearls which are fornaed on buccal mass, gonad and mantle. The frequency of occurrence of pearls in larger individuals is greater than that in smaller individuals. The pearls are lustrous and in most cases are spherical. Most of the pearls are smaller than 3 mm.